2016
DOI: 10.1016/j.arth.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Damage Done to Bone by Burring and Sawing With and Without Irrigation in Knee Arthroplasty

Abstract: These results suggest that irrigating bone during resection could prevent osteonecrosis onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Irrigated, low-speed, low-force cutting devices should be used to prevent overheating of the specimens, and thus reduce thermal and mechanical damage. 9 , 204 Diamond is a material that has been shown to be resistant to wear 205 and is biocompatible. 206 Thus, where possible, this should be used for tool materials.…”
Section: Discussionmentioning
confidence: 99%
“…Irrigated, low-speed, low-force cutting devices should be used to prevent overheating of the specimens, and thus reduce thermal and mechanical damage. 9 , 204 Diamond is a material that has been shown to be resistant to wear 205 and is biocompatible. 206 Thus, where possible, this should be used for tool materials.…”
Section: Discussionmentioning
confidence: 99%
“…This physiological repair mechanism is also effective in the event of thermal damage to the bone. Surgical procedures often involve the risk of overheating [4,5]. Cutting, rotating, and vibrating instruments are used regularly in contact with the hard and soft tissue under cooling [6].…”
Section: Introductionmentioning
confidence: 99%
“…Prior testing of bovine and caprine trabecular bone samples confirmed that this method yielded a sufficiently polished surface for nanoindentation. Care was taken to ensure that the post-polishing thicknesses of the subject's medial and lateral samples were the same and that at least 0.5 mm of bone was ground to remove the regions damaged by the oscillating surgical saw 27 . After grinding, the samples were cleaned in the ultrasonic bath for 5 min, then put back in the tubes and kept refrigerated at 4 °C before the indentation phase began.…”
Section: Methodsmentioning
confidence: 99%